Simplify. 5–1(3–2) Please help!!!!

1 answer

To simplify this expression, we need to follow the order of operations (also known as PEMDAS).

- Parentheses: There are parentheses in the expression. Evaluate what's inside them first.
3 - 2 = 1

- Exponents: There are no exponents in the expression.

- Multiplication and Division: There is multiplication involved (5 * (1)).
5 * 1 = 5

- Addition and Subtraction: There is no addition or subtraction involved.

Now that we have simplified each part, we can combine them:
5 - 1 * 1

Finally, we perform the multiplication:
5 - 1 = 4

Therefore, the simplified expression is 4.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions